ANALYSIS OF THE ASSIMILATION AND INTEGRATION POLICIES OF PRISONS IN THE PREVEBTION AND SPREAD OF COVID-19 - Ria Shelawati; Bambang Utoyo; Intan Fitri Meutia (KOLONI, 2022)
The assimilation and integration of prisons is aimed at overcoming and spreading the covid virus during the current pandemic. The purpose of this study is to analyze the Assimilation and Integration Policy of Prisons in Combating and Spreading Covid-19 using William N Dunn's policy evaluation indicators, namely: 1) effectiveness, 2) efficiency, 3) adequacy, 4) equity/equality, 5) responsiveness, 6) accuracy. This study uses a qualitative approach with a descriptive type. Data collection techniques through interviews, observation and documentation. The results of the study indicate that the implementation of the assimilation and integration policy of the prison has been going well. This is shown from the 6 (six) indicators of Dunn's policy evaluation, only indicators of adequacy and responsiveness indicators are still not running well. Judging from the adequacy indicator, there are still some problems that have not been resolved, while from the responsiveness indicator, community participation in this program is still very low due to the fear of people with redivis who fear they will commit crimes again. The recommendation from this research is that the Ministry of Law and Human Rights and prisons provide very serious assistance and guidance to prospective assimilation recipients so that in the future they will not repeat the crime again. Keywords: Policy Analysis, Policy Evaluation, Assimilation and Integration Policy